EXPLORING THE INFLUENCE OF PARENTAL-TEACHER ENGAGEMENT IN PLAY-BASED MATHEMATICAL LEARNING ON MOTOR DEVELOPMENT AND HEALTH OUTCOMES IN EARLY CHILDHOOD - Sari, Diah Andika; Kuswanto, Cahniyo Wijaya; Anhusadar, Laode; Purnama, Sigit; Ulfah, Maulidya (LPPM Universitas Jambi, 2025)
This study examines the influence of parental-teacher engagement in play-based mathematical learning on the motor development and health outcomes of preschoolers. The research is grounded in socio-cultural and ecological systems theory, responding to the growing need for holistic, collaborative approaches in early childhood education that integrate academic, behavioral, and physical domains. Using a mixed-method sequential explanatory design, the study was conducted over three months in three early childhood centers in Bandar Lampung, Indonesia, involving 120 children aged 4–6 years, along with their teachers and parents. Quantitative data were collected using the Peabody Developmental Motor Scales–Second Edition (PDMS-2), a WHO-adapted Health Monitoring Checklist, and a validated observation rubric on adult collaboration. Results showed significant improvements in gross and fine motor skills (Cohen’s d = 1.98–2.63), and in health behaviors, including increased physical activity (+28%), healthier eating habits (+25%), and more consistent sleep routines (+13%). Based on semi-structured interviews and focus groups with 25 participants, the qualitative phase revealed themes such as strengthened home-school partnerships, embedded learning in daily routines, enhanced child engagement, and challenges related to time and resources. The study concludes that collaborative, play-based learning environments effectively support integrated child development, with sustained benefits when reinforced across home and school. These findings empirically support family-inclusive pedagogies and suggest the need for differentiated engagement models and longitudinal follow-up to maximize developmental outcomes.